2015
DOI: 10.3389/fmicb.2015.00905
|View full text |Cite
|
Sign up to set email alerts
|

Wine fermentation microbiome: a landscape from different Portuguese wine appellations

Abstract: Grapes and wine musts harbor a complex microbiome, which plays a crucial role in wine fermentation as it impacts on wine flavour and, consequently, on its final quality and value. Unveiling the microbiome and its dynamics, and understanding the ecological factors that explain such biodiversity, has been a challenge to oenology. In this work, we tackle this using a metagenomics approach to describe the natural microbial communities, both fungal and bacterial microorganisms, associated with spontaneous wine ferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
173
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(207 citation statements)
references
References 53 publications
(66 reference statements)
25
173
1
1
Order By: Relevance
“…These authors even predicted the metabolome of the wine from the microbial composition by using machine learnig techniques [54]. Similar results have also been generated from other studies [55,56].…”
Section: Analysis Of Alcoholic Fermentationsupporting
confidence: 72%
See 2 more Smart Citations
“…These authors even predicted the metabolome of the wine from the microbial composition by using machine learnig techniques [54]. Similar results have also been generated from other studies [55,56].…”
Section: Analysis Of Alcoholic Fermentationsupporting
confidence: 72%
“…Even though there is no clear answer to this debate, studies from Suárez et al [64] and Pinto et al [56] seem to support the latter hypothesis.…”
Section: Analysis Of Alcoholic Fermentationmentioning
confidence: 97%
See 1 more Smart Citation
“…Taxonomical assignments showed that most OTUs found in the Chilean vineyard samples corresponded to the fungal and bacterial species commonly found in grapes or grape must in various world wine regions (Bokulich et al ., ; Taylor et al ., ; Piao et al ., ; Pinto et al ., ; Portillo et al ., ). Relative abundance analysis of the fungal OTUs showed that Dothideomycetes was the most abundant taxonomical class, which made up 78%–96% of the total sequences of each sample (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…For example, indigenous yeasts and lactic and acetic bacteria living in grapes greatly affect the aroma of wine (Knight et al, 2015;Vigentini et al, 2016), and the epiphyte fungal and bacterial diversity of leaves are closely related to the health status of grapevines (Pinto et al, 2014). Recently, several studies have shown that regional differences in grape microbial community compositions, so called 'microbial terroir' (Bokulich et al, 2014;Gilbert et al, 2014;Taylor et al, 2014;Morrison-Whittle and Goddard, 2015;Pinto et al, 2015) are significantly correlated with the regional characteristics of wine flavour (Knight et al, 2015;Bokulich et al, 2016). However, there is little discussion as to why the microbial community composition of wine grapes is differentiated at regional or broad spatial scales (but see Morrison-Whittle and Goddard, 2015).…”
Section: Introductionmentioning
confidence: 99%